2015
DOI: 10.1515/hepo-2015-0031
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial and antioxidant activities of extracts obtained from some moss species in Turkey

Abstract: SummaryIntroduction:Pharmaceutical industry is forced to develop new pharmacologically active molecules. Like other plants, mosses are considered to be potential source of new biologically active compounds.Objective:The present study was designed to evaluate the antimicrobial and antioxidant activity of 8 moss species:Hypnum cupressiforme, Homalothecium sericeum, Thuidium delicatulum, Homalothecium lutescens, Homalothecium nitens,Leucodon sciuroides, Ctenidium molluscum,andEurhynchium striatulumobtained from T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
1
18
2
2
Order By: Relevance
“…An additional, but so far hypothetical, reason for bryophyte selection could be their possible use as a defense against pathogens (Dubiec et al 2013;D'Alba and Shawkey 2015). As extracts from several moss species show strong antimicrobial activity in the lab (Bukvički et al 2012;Ertürk et al 2015;Klavina et al 2015), they could probably show some anti-pathogen activity in nature as well, and the birds might use those species exhibiting the strongest such properties.…”
Section: Plant Speciesmentioning
confidence: 99%
“…An additional, but so far hypothetical, reason for bryophyte selection could be their possible use as a defense against pathogens (Dubiec et al 2013;D'Alba and Shawkey 2015). As extracts from several moss species show strong antimicrobial activity in the lab (Bukvički et al 2012;Ertürk et al 2015;Klavina et al 2015), they could probably show some anti-pathogen activity in nature as well, and the birds might use those species exhibiting the strongest such properties.…”
Section: Plant Speciesmentioning
confidence: 99%
“…Depending on these factors, antioxidant amounts in the species vary both within themselves and between species [30]. The study on the total free radical scavenging activity of Eurhynchium striatulum and Homalothecium sericeum showed that these have very strong free radical scavenging activity [31].…”
Section: Antioxidant Property In Bryophytesmentioning
confidence: 99%
“…Bryum argenteum (nbutanol extract, among four extracts) has considerable antibacterial activity. 80 Some non-local species have been studied for their antioxidant 81 and anti-inflammatory activities. 82 The case of Colchicacea family is one of the strangest and most interesting.…”
Section: Plant Materials Preparation Extractionmentioning
confidence: 99%